2016
DOI: 10.4067/s0718-95162016005000077
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of native arbuscular mycorrhizal consortia on the growth of Agave inaequidens

Abstract: The aim of this study was to evaluate the effect of eight native consortia of arbuscular mycorrhizal fungi (AMF), a commercial strain and a control without AMF on the growth of Agave inaequidens. Agave seedlings were inoculated and kept under greenhouse conditions for 300 days. At 90, 180 and 270 days after inoculation, the number of leaves and plant height were recorded; at the end of the experiment, fresh and dry weight, head (also known as heart or piña) diameter, leaf area and root length and volume were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
0
19
0
4
Order By: Relevance
“…Man et al (2011) and that the morphological conditions of the plant are enhanced by their roots. This enhancement can also be explained by the secretion of glomalin that contributes to a better uptake of water and nutrients by the plant (Cornejo et al, 2017;Durán et al, 2016;Miransari, 2014;Quiñones-Aguilar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Man et al (2011) and that the morphological conditions of the plant are enhanced by their roots. This enhancement can also be explained by the secretion of glomalin that contributes to a better uptake of water and nutrients by the plant (Cornejo et al, 2017;Durán et al, 2016;Miransari, 2014;Quiñones-Aguilar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In general, this study found an increase in guava plants propagated by seeds when a mycorrhizal consortium was applied. The effectiveness of some of this native consortia has been proven in maize, chili, and bean (Reyes-Tena et al, 2015, Agave inaequidens (Quiñones-Aguilar et al, 2016), and Agave cupreata (Trinidad-Cruz et al, 2017b). This promotion effectiveness may have been caused by the diversity of the AMF species that contain inoculants; with this respect, Gavito and Varela (1995) and Bashan et al (2000) mentioned that the inoculants constituted by more than one AMF species showed a greater benef it in their hosts.…”
Section: Guava Plant Growthmentioning
confidence: 98%
“…Furthermore, native mycorrhizal consortia are also known to be more effective than those constituted by exotic species or only one species (Bashan et al, 2000;Ortas and Ustuner, 2014). et al., 2015, 2016), Agave inaequidens (Quiñones-Aguilar et al, 2016) y Agave cupreata (Trinidad-Cruz et al, 2017b). Esta efectividad en la promoción puede deberse a la diversidad de especies de HMA que contienen los inóculos; ante esto Gavito y Varela (1995) y Bashan et al (2000) mencionan que los inóculos constituidos por más de una especie de HMA, presentan un mayor benef icio en sus hospedantes.…”
Section: Guava Plant Growthunclassified
“…Al respecto, existen estudios que indican que a pesar de que el genoma de la papaya determina la dependencia micorrízica, ya que distintas variedades inoculadas con los mismos HMA y dosis de P responden diferencialmente a la micorrización (Trindade et al, 2001), también la especie de HMA es importante para inducir esta respuesta (Khade y Rodrigues, 2009). Quiñones-Aguilar et al (2016) mostraron que los inóculos CM y AD tuvieron una dependencia micorriza alta empleando como planta hospedera a Agave inaequidens. Estos últimos datos en conjunto con los obtenidos en el presente estudio apuntan hacia la existencia de diferentes niveles de af inidad entre la especie vegetal y las especies o consorcios de HMA.…”
Section: íNdice Relativo De Dependencia Micorrízica (Irdm) De Papaya unclassified